Studi Agronomis Tanaman Padi (Oryza sativa L.) Hasil Ko-Kultivasi Beberapa Strain Agrobacterium tumefaciens - Pupita Deswina; Inez H. Slamet Loedin (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2011)
The transgenic rice of Cisadane and Rajalele cultivars (cv) was obtained by co-cultivation of rice callus by 4 strain Agrobacterium tumefaciens containing 4 different binary vector (pIG 121 Hm, pCAMBIA 1301, pTOK 233 and pMOG22 BarGus). The transgenic plantlets were acclimatized and grown in the growth chamber to investigate their agronomic characteristic in comparison to control plants. The results showed that there was no difference in the number of spikelet and seeds/spikelet among different transgenic lines co-cultivated by different strains. The number of seed/spikelet of transgenic rice cv. Rojolele and Cisadane compared to their control did not show significant difference. However, the total number of spikelet was different only for cv. Rojolele.